Appreciative Inquiry Approach in Limited Face-To-Face Learning at SMAN 1 Pusakanagara - Dyah Tri Susilawati; Tono Prayogo; Anwar Shidiq Santoso (research, training and philanthropy institution Natural Aceh, 2022)
This research is intended as a response to limited face-to-face learning which is a new model in the learning system, this is intended as a reaction in preventing the transmission of COVID-19. As a learning model that has just been implemented, of course, there will be many obstacles faced theoretically and technically. Therefore, a proactive effort is needed to answer the challenges in limited face-to-face learning. The teacher's adaptive attitude in terms of pedagogy and professionalism is needed as a solution. One of the steps that can be taken is to use an appreciative inquiry approach to find a learning model that remains limited to face-to-face learning. This study uses a descriptive qualitative method with an appreciative inquiry approach that will reveal a limited face-to-face learning model that is following the characteristics of students at SMAN 1 Pusakanagara. This study involved 369 respondents from a total population of 1,080 respondents by taking samples of three groups (study groups) at each level. The data was obtained through a questionnaire distributed via a google form, then reduced and analyzed. The period of this research is September to December 2021. The stages of appreciative inquiry are defined, discovery, dream, design, and destiny or delivery. Based on the analysis using an appreciative inquiry approach, it is concluded that several face-to-face learning models are limited at SMAN 1 Pusakanagara, including direct practice learning models, project-based learning models, problem-based learning models, and inquiry learning models.